2016
DOI: 10.1016/j.bbapap.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the binding interface between leiomodin-2 and α-tropomyosin

Abstract: The development of some familial dilated cardiomyopathies (DCM) correlates with the presence of mutations in proteins that regulate the organization and function of thin filaments in cardiac muscle cells. Harmful effects of some mutations might be caused by disruption of yet uncharacterized protein-protein interactions. We used nuclear magnetic resonance spectroscopy to localize the region of striated muscle α-tropomyosin (Tpm1.1) that interacts with leiomodin-2 (Lmod2), a member of tropomodulin (Tmod) family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(63 citation statements)
references
References 59 publications
6
57
0
Order By: Relevance
“…However, biochemical and cellular studies have shown that the interaction of Lmods with TM through TMBS1 enhances slightly Lmods' nucleation activity (Fig. 2 F), and is also critical for proper localization in muscle sarcomeres (3,6,40,41,43). On the other hand, the region structurally visualized as ABS1 in Tmod (human Tmod1 residues P58-K99) is only partially conserved in Lmods (Fig.…”
Section: Contribution Of the N-terminal Region To Tm Binding And Nuclmentioning
confidence: 99%
See 1 more Smart Citation
“…However, biochemical and cellular studies have shown that the interaction of Lmods with TM through TMBS1 enhances slightly Lmods' nucleation activity (Fig. 2 F), and is also critical for proper localization in muscle sarcomeres (3,6,40,41,43). On the other hand, the region structurally visualized as ABS1 in Tmod (human Tmod1 residues P58-K99) is only partially conserved in Lmods (Fig.…”
Section: Contribution Of the N-terminal Region To Tm Binding And Nuclmentioning
confidence: 99%
“…Studies using NMR and CD spectroscopy suggest that the intrinsically disordered TMBSs adopt a helical conformation upon binding to the N-terminal $35 aa of the TM coiled coil (32), substituting for end-to-end interactions of TM molecules along the length of the actin filament (34,35). ABS2 is contained within the C-terminal region (residues $160 onward), which has a globular fold consisting mostly of a leucine-rich repeat (LRR) domain (36 very weakly compared to Lmods (3,6,16 (3,6,(40)(41)(42)(43), but lack the conserved TMBS2 of Tmods, with the corresponding region varying widely among Lmod isoforms, and displaying an abundance of negatively charged amino acids (Glu and Asp). Lmod1, in particular, presents a large insertion of >200-aa within this region, which curiously may contain a divergent TMBS, because a fragment of Lmod1 missing the first 30 aa still binds TM (26).…”
Section: Domain Organization and Biochemical Activity Of Tmodsmentioning
confidence: 99%
“…The construct for αTM1a 1-21 Zip was prepared as described previously [9]. The αTM1a 1-21 Zip peptide contained the 21 N-terminal residues of the striated muscle α-Tpm (Tpm1.1) and 18 residues of the leucine zipper domain of the yeast transcription factor GCN4 [28] to stabilize a coiled-coil structure in solution [29].…”
Section: Methodsmentioning
confidence: 99%
“…The construct for the αTM1a 1-21 Zip[K15N] peptide was prepared by site-directed mutagenesis [9]. The construct for rat striated muscle α-Tpm (Tpm1.1) was a generous gift from Dr. Sarah Hitchcock-DeGregori (Rutgers University, Piscataway, NJ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation